Legal framework for construction dispute resolution in Nigeria : a reform oriented analysis - Raji, Barakat Adebisi (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
This research studied the benefits of adopting ADR mechanisms specially designed for dispute resolution in the construction in Nigeria. It also identified problems of using ADR mechanisms and solutions to mitigate such problems. In order to achieve these objectives, the study gathered information from both primary and secondary sources. The study used mixed mode for data collection which consist of both structured interview and survey in order to collect more data. Hence, Fifteen (15) construction experts were interviewed consisting of legal practitioners, stakeholders and judges who have been into construction practice for more than ten (10) years were selected using purposive technique to get rich data. The findings revealed the inadequacy of the legal framework for construction dispute resolution in Nigeria. This has led to the abandonment of many of the projects across the country as well as claiming the lives and properties of some stakeholders. In addition to triangulate the data, five hundred questionnaires were self-administered to other stakeholders out of which three hundred and seven responses were analysed. The statistical analysis was performed on the data collected using SPSS to assess the effects of various parameters on ADR mechanism. From the statistical analysis carried out, the result revealed that 61% responses represent effective response rate and adequate for this study. While 91% of the respondents supported the use of ADR mechanisms in the attainment of dispensation of justice system in construction dispute resolution in Nigeria. The research has shown that the use of ADR will go a long way in resolving the disputes associated with construction industry in Nigeria. It is evident that ADR mechanisms would make a remarkable contribution to the existing practice of the construction dispute resolution in Nigeria. Hence, this study recommends the provisions of the ADR mechanisms specially designed for disputes management in construction industry urging the policy makers and the stakeholders in the industry to contribute in this direction in order to ensure cost-effective and time-bound resolution mechanism that will rank the industry among its counterparts.